OC-065 Motility and Oesophageal Clearance in Barrett's Oesophagus. (17th August 2016) - Sweis, R; Raeburn, A; Athanasakos, E; Zarate-Lopez, N; Lovat, L; Haidry, R; Banks, M; Emmanuel, A
Abstract : Introduction: It is not clear if Barrett's is a consequence of excessive reflux only or reduced clearance of refluxed materials. This study compares oesophageal reflux over 24 hours and High Resolution Manometry (HRM) response to solids in Barrett's with non-Barrett's reflux (NBR). Methods: Reports for 19 consecutive patients (M58:F14) with ≥2 cm Barrett's during 2015 were compared with 25 patients with NBR (M10:F16) and 13 patient controls with normal physiology/endoscopy (M3:F10). All had at least one typical symptom of heartburn, regurgitation or chest pain. All had HRM with the intention of completing 10x5cc water and 5x1cc bread. Contractile vigour was measured with the Distal Contractile Integral (amplitude x length x contraction time); DCI > 450 mmHg.cm.s and breaks in peristalsis of <5 cm were considered the lower limit of normal contraction as per Chicago Classification 3.0. Standard reflux and impedance parameters were assessed. 11/19 Barrett's were on while all NBR were off treatment. Results: Lower oesophageal sphincter pressure was lower in Barrett's (8 vs. 14 mmHg; p = 0.009). Compared to NBR, patients with Barrett's (2–10 cm) had significantly reduced DCI for both 5 ml water (318 vs. 650 mmHg.cm.s; p = 0.007) and solid (1096 vs. 2002 mmHg.cm.s; p = 0.009). On the other hand, the likelihood of measuring a DCI of >450 was significantly reduced in Barrett's only with solids (69% vs. 100%; p < 0.001) not water (32% vs. 54%; p = 0.224). Peristaltic effectiveness based on HRM was also reduced only for solids (44% vs. 65%; p = 0.029). All reflux parameters were similar between the two groups: total (p = 0.116), upright (p = 0.233) and supine reflux (p = 0.110), symptom index (p = 0.16), symptom association probability (p = 0.106) and total number of reflux events (p = 0.063). On the other hand, bolus clearance time (BCT) was significantly prolonged for Barrett's (13 vs. 10 s; p = 0.009) solely due to prolonged supine BCT (14 vs. 10 s; p < 0.003). Bolus exposure time (BET) was significantly prolonged for Barrett's (p = 0.011) due to both daytime (4.49% vs. 1.73%; p = 0.015) and nocturnal BET (0.75% vs. 0.24%; p = 0.002). Comparing those with prior endoscopic Barrett's therapy (n = 6) with treatment naïve (n = 13), there was no difference in any motility or pH monitoring parameter apart from BET which was greater in those who received therapy (5.87% vs. 1.99%; p = 0.046). Conclusion: Solids were superior to water swallows in demonstrating ineffective contractility in Barrett's. This was associated with reduced nocturnal oesophageal clearance and increased exposure to refluxate during the day/night. These findings contribute to the theory of impaired contractility and reduced clearance despite acid-reducing medication in Barrett's. Disclosure of Interest: R. Sweis Conflict with: Organised Symposium funded by Given img/Diagmed, A. Raeburn: None Declared, E. Athanasakos: None Declared, N. Zarate-Lopez: None Declared, L. Lovat: None Declared, R. Haidry: None Declared, M. Banks: None Declared, A. Emmanuel: None Declared